2016
DOI: 10.1016/j.ijid.2016.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological trends and characteristics of Japanese encephalitis changed based on the vaccination program between 1960 and 2013 in Guangxi Zhuang Autonomous Region, southern China

Abstract: Japanese encephalitis (JE) is one of the most severe kinds of viral encephalitis and is prevalent in Asia and the Western Pacific. In China, JE was first reported in the 1940s and became the main cause of viral encephalitis, including in the Guangxi Zhuang Autonomous Region. In 1951, JE was included in the Chinese mandatory disease reporting system. In the pre-vaccine era of the 1960s and 1970s, the incidence of JE continued to rise without any vaccine supply. Since JE vaccines became available in the late 197… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Pig rearing is a known risk factor for Japanese Encephalitis virus, because pigs are an important amplifying host. Studies conducted in India [ 10 , 11 , 12 ], Republic of Korea [ 13 , 14 ], Nepal [ 15 ], and China [ 16 ] showed the same results. The need for the vaccination of local residents and pigs against JEV is often considered [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 64%
“…Pig rearing is a known risk factor for Japanese Encephalitis virus, because pigs are an important amplifying host. Studies conducted in India [ 10 , 11 , 12 ], Republic of Korea [ 13 , 14 ], Nepal [ 15 ], and China [ 16 ] showed the same results. The need for the vaccination of local residents and pigs against JEV is often considered [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 64%
“…China was one of the most prevalent countries for JE in 1950s–1960s [16, 17]. Since JE vaccine became available in the late 1970s, the incidence of JE has declined significantly [18]. In 1980, China participated in the Expanded Program on Immunization (EPI) of WHO.…”
Section: Discussionmentioning
confidence: 99%
“…Vaccine is the most effective and economic way in preventing infectious diseases [2426]. Studies have shown that the routine use of JE vaccines results in dramatic decrease of cases and incidence rates [27–29]. Shift of cases to adults (as opposed to children) indicate that the older age groups are now at more risk of JE than the target population.…”
Section: Discussionmentioning
confidence: 99%